Hubungan Kebiasaan Sarapan Pagi dengan Status Gizi pada Siswa di SD Muhammadiyah Kayen - Kania Valisa; Agung Nugroho; Ibtidau Niamilah (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
Breakfast is an important habit that plays a major role in meeting children's energy and nutritional needs. The energy obtained from breakfast is essential for daily activities, including learning and playing, enabling children to achieve optimal performance both physically and cognitively. Furthermore, breakfast habits also contribute to children's nutritional status, reflecting the balance between nutritional intake and needs. However, the reality shows that in Indonesia, approximately 40% of children still do not have breakfast before going to school, potentially affecting their nutritional status. This study aims to determine the relationship between breakfast habits and the nutritional status of students at Muhammadiyah Kayen Elementary School. The study used a quantitative approach with a cross-sectional design and utilized primary data. The study population was all 225 students in grades I to IV. Of these, 112 students were selected through a purposive sampling technique. Data were collected using a questionnaire to explore breakfast habits and anthropometric measurements of height and weight to determine nutritional status. Data analysis was performed using the Fisher exact test. The results showed a p-value of 0.742 (p > 0.05), indicating no significant relationship between breakfast habits and students' nutritional status. A total of 79.5% of students had good breakfast habits, while 20.5% were classified as adequate. Meanwhile, the students' nutritional status consisted of good nutrition (57.1%), overnutrition (19.7%), obesity (11.6%), malnutrition (8%), and undernutrition (3.6%). Thus, it can be concluded that breakfast habits are not significantly related to the nutritional status of students at the school.